2010
DOI: 10.1111/j.1600-6143.2010.03128.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Withdrawal of Calcineurin Inhibitors and Everolimus Monotherapy in de novo Liver Transplant Recipients Preserves Renal Function

Abstract: We designed a randomized trial to assess whether the early withdrawal of cyclosporine (CsA) followed by the initiation of everolimus (Evr) monotherapy in de novo liver transplantation (LT) patients would result in superior renal function compared to a CsA-based immunosuppression protocol. All patients were treated with CsA for the first 10 days and then randomized to receive Evr in combination with CsA up to day 30, then either continued on Evr monotherapy (Evr group) or maintained on CsA with/without mycophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
188
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(195 citation statements)
references
References 32 publications
4
188
1
2
Order By: Relevance
“…Together, these studies suggest that liver transplant patients can receive a renal benefit from everolimus initiation with CNI withdrawal even at a relatively late stage after transplantation unless renal deterioration is profound. The remarkable improvement in eGFR (almost 30 mL/minute) reported by Masetti et al 16 after CNI withdrawal on day 30 in everolimus-treated patients versus CNI-treated patients highlights that early, preemptive conversion may be a more promising strategy. The second major indication for the introduction of everolimus was the prevention or treatment of malignancies; this reflects current interest in the role of mTOR inhibitors in the management of posttransplant tumors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Together, these studies suggest that liver transplant patients can receive a renal benefit from everolimus initiation with CNI withdrawal even at a relatively late stage after transplantation unless renal deterioration is profound. The remarkable improvement in eGFR (almost 30 mL/minute) reported by Masetti et al 16 after CNI withdrawal on day 30 in everolimus-treated patients versus CNI-treated patients highlights that early, preemptive conversion may be a more promising strategy. The second major indication for the introduction of everolimus was the prevention or treatment of malignancies; this reflects current interest in the role of mTOR inhibitors in the management of posttransplant tumors.…”
Section: Discussionmentioning
confidence: 94%
“…15 One randomized trial assessed the impact of converting 78 patients from CNI therapy to everolimus very early (day 30) after liver transplantation. 16 Renal function was significantly better at 1 year in the everolimus cohort, and this improvement was accompanied by a lower incidence of chronic kidney disease (stage 3 or higher); however, the rate of acute rejection was similar to the rate for the CNI arm. Single-arm studies have demonstrated that maintenance liver transplant patients can be converted from CNIs to everolimus safely at later time points with a low rate of acute rejection.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, subsequent single-center observational studies (not clinical trials) comparing de novo sirolimus initiation at time of LTx have not shown an increased risk of graft failure or HAT as compared to other strategies, which underscore the importance of making the data of this multicenter study available to clinicians (15,20). Second, given emerging literature on the role of another mTOR inhibitor, everolimus, it is important to gauge whether similarities exist in the risk and benefit profile for these two medications (21)(22)(23)(24)(25)(26)(27). Above all, transparency in the full presentation of the results of the study are important given that it may impact our current approach to management of immunosuppression after LTx.…”
Section: Introductionmentioning
confidence: 99%
“…Promising protocols include sirolimus, MMF, and steroids or the combination of anti-CD25 antibodies, sirolimus, MMF, and steroids. These protocols have shown acceptable graft survival rates and acute rejection rates; however, these studies were small in size and further research is warranted [34]. In short, multiple regimens have been shown to be effective.…”
Section: Calcineurin Inhibitor-free Protocolsmentioning
confidence: 99%